The role of foot and ankle assessment of patients with lower limb osteoarthritis. - Reilly, K; Barker, K; Shamley, D; Newman, M; Oskrochi, G; Sandall, S (2009)
OBJECTIVES: Physiotherapists do not routinely examine the feet of patients with lower limb osteoarthritis, and there is no widely used tool for measuring foot posture. However, differences in foot posture have been demonstrated between patients with medial compartment osteoarthritis of the knee and osteoarthritis of the hip, and guidelines for managing these patients include interventions such as orthotics which presume foot assessment. This study considers a new clinical tool, the Foot Posture Index (FPI). It examines its utility in a physiotherapy outpatient setting with a cohort of patients with medial compartment osteoarthritis of the knee and osteoarthritis of the hip, and investigates the relationship of FPI scores with the range of dorsiflexion of the ankle. DESIGN: Cross-sectional observational study. SETTING: A specialist orthopaedic hospital. PARTICIPANTS: In total, there were 60 participants: 20 patients with medial compartment osteoarthritis of the knee, 20 patients with osteoarthritis of the hip, and a control group of 20 age-matched healthy volunteers. OUTCOME MEASURES: A single measurement of the FPI and range of dorsiflexion. RESULTS: Significant differences in FPI scores and range of dorsiflexion were seen between groups. On average, patients with osteoarthritis of the hip had more supinated, plantarflexed feet, and patients with medial compartment osteoarthritis of the knee had pronated feet. Healthy controls fell within the normal range. Patients with osteoarthritis of the hip had a median FPI score of -4.5, patients with medial compartment osteoarthritis of the knee had a median FPI score of 7.0, and the healthy controls had a median FPI score of 1.0. The median difference in FPI scores between patients with osteoarthritis of the hip and medial compartment osteoarthritis of the knee was 12 [95% confidence interval (CI) 10 to 13]; between patients with osteoarthritis of the hip and the healthy group was 6 (95% CI 3 to 9); and between patients with medial compartment osteoarthritis of the knee and the healthy group was 5 (95% CI 3 to 8). The median difference in dorsiflexion scores between patients with osteoarthritis of the hip and medial compartment osteoarthritis of the knee was 10 degrees (95% CI 8 to 15); between patients with osteoarthritis of the hip and the healthy group was 10 degrees (95% CI 7 to 15); and between patients with medial compartment osteoarthritis of the knee and the healthy group was 0 degrees (95% CI -3 to 5). Foot posture and range of dorsiflexion were moderately positively correlated (rho 0.57), with pronated feet having a greater range of dorsiflexion. CONCLUSION: The FPI is sufficiently sensitive to measure differences in foot posture of patients with medial compartment osteoarthritis of the knee and osteoarthritis of the hip, and is easy to use. Accurate foot assessment is useful as foot postures may be influenced by specific physiotherapy treatment modalities and orthotic interventions.